2007
DOI: 10.1002/pen.20814
|View full text |Cite
|
Sign up to set email alerts
|

Application of essential work of fracture concept to toughness characterization of high‐density polyethylene

Abstract: Deformation and fracture toughness of high-density polyethylene (HDPE) in plane-stress tension was studied using the concept of essential work of fracture (EWF). Strain range for necking was determined from uniaxial tensile test, and was used to explain the deformation transition for 2-staged crack growth in doubleedge-notched tensile test. Through work-partitioning, EWF values for HDPE were determined for each stage of the crack growth. Appropriateness of these EWF values to represent the material toughness i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 24 publications
1
23
0
1
Order By: Relevance
“…Previous studies evaluating the EWF of polyethylene such as HDPE [6,11,12] have neglected the process of neck developing in analyzing the energy needed during the fracture. In contrast to those studies, Jar and co-workers [13,14] have observed neck formation during fracture process and reported that in plane stress fracture of DENT specimen, the neck was initiated along the ligament part, it spread to adjacent areas which had been deformed at an early step of the test.…”
Section: Introductionmentioning
confidence: 72%
See 3 more Smart Citations
“…Previous studies evaluating the EWF of polyethylene such as HDPE [6,11,12] have neglected the process of neck developing in analyzing the energy needed during the fracture. In contrast to those studies, Jar and co-workers [13,14] have observed neck formation during fracture process and reported that in plane stress fracture of DENT specimen, the neck was initiated along the ligament part, it spread to adjacent areas which had been deformed at an early step of the test.…”
Section: Introductionmentioning
confidence: 72%
“…It can be elucidated as follows. Strain increment (dε) in the plastic zone can be obtained from the relationship as follows [14,28,29]:…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several test methods have been designed based on the concept, to separate the energy consumed in the fracture process zone (FPZ) from the other forms of energy consumption during the crack growth, including that for the global plastic deformation in ductile fracture (Kwon and Jar 2006a). Currently, double-edge-notched tensile test (DENT test) is the most popular method based on the EWF concept, and has been successfully used to quantify toughness for ductile fracture in mode I, commonly known as specific essential work of fracture (w I e ).…”
Section: Essential Work Of Fracture (Ewf)mentioning
confidence: 99%